Bioprosthetic aortic valve leaflet disruption with high energy electrocautery to prevent coronary artery obstruction during valve‐in‐valve transcatheter aortic valve replacement. Issue 1 (8th October 2018) - Nelson, Bradley C.; Chadderdon, Scott; Song, Howard; Zahr, Firas E.
Abstract: Transcatheter aortic valve replacement (TAVR) is well‐established for the treatment of bioprosthetic aortic valve stenosis (AS) in high surgical risk patients. Coronary artery obstruction from displacement of the bioprosthetic valve leaflets during valve‐in‐valve (VIV) TAVR is a rare, but potentially fatal, complication. Recently, the bioprosthetic aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction (BASILICA) procedure was developed as a method for disrupting bioprosthetic leaflets in patients undergoing VIV TAVR at high risk for coronary obstruction. This case describes a successful VIV TAVR utilizing a simplified concept of the BASILICA technique in a patient where the full procedure could not be completed.